The Nature of the Aims of Education: Quranic Perspectives - Nakib, Omar (Al-Bayān, 2015)
This study is concerned with analyzing the aims of education in the Qurʾān. It involves an investigation into relevant Quranic verses and their exegesis. Due to the nature of the research problem, a qualitative methodology has been adopted, and content analysis employed to examine the data when addressing the research questions. The questions addressed are: How does the Qurʾān treat the aims of education? What are the main aims of education that are treated by the Qurʾān? What are the practical implications of this on developing an Islamic education curriculum? The findings of this study show that the Qurʾān, as well as the Sunna, has prescribed a range of aims for education, distinguished into three important aspects: constancy, consistency, and universality through harmonizing, integrating, and encompassing the different dimensions of the human personality. The Qurʾān has a particular view of man since it deals with human nature from a realistic perspective, one which takes the human being as he really is, as regards all aspects of his personality: spiritual, material, and intellectual. To conclude, and to elucidate the implications of the findings on the development of an Islamic education curriculum, this study emphasizes the need to preserve the originality of Quranic teachings and their feasibility in order to actualize the meanings of the Qurʾān in human life. The curriculum should clearly reflect these aims in such a way that educational practitioners should be able to actualize the desired model of man as prescribed by the Qurʾān.